Descriptive Analysis of Access to Proper Sanitation Facilities (Healthy Latrines) and the Incidence of Diarrhea in the Working Area of Batuatas Health Center, 2022–2024 - Ramadhan Tosepu; Ardiansyah Mahlia; Ida Royani Sampulawa; Herli Anita (Journal of Health Science and Pharmacy, 2026)
Background: Diarrhea remains a major public health problem in Indonesia, particularly in coastal and island regions with limited access to sanitation. The low ownership of healthy latrines is an environmental factor contributing to the high incidence of diarrhea. South Buton Regency, especially the working area of Batuatas Health Center, has challenging coastal geographical conditions, making it vulnerable to sanitation and environmental health problems. Objective: This study aims to describe the distribution of access to healthy latrines and the incidence of diarrhea in the working area of Batuatas Health Center during the period 2022–2024, based on secondary data from the Health Center Profile Methods: This is a quantitative descriptive study using secondary data from the Batuatas Health Center Profile. The data analyzed include the percentage of households with healthy latrines and the incidence rate of diarrhea across all age groups. The analysis was conducted using tables and graphs to interpret patterns and trends narratively. Result: The coverage of healthy latrines decreased from 77.45% in 2022 to 64.04% in 2024. Conversely, the incidence of diarrhea increased from 23.15 per 1.000 population in 2022 to 24.25 per 1.000 population in 2024. Conclusion: Access to healthy latrines is closely related to the incidence of diarrhea. A decrease in healthy latrine coverage has the potential to increase the risk of diarrhea in Batuatas. Efforts in education, community empowerment, and strengthening the Community-Based Total Sanitation program need to be continuously improved, especially in coastal areas with limited sanitation facilities. These results are expected to be the basis for environmental health intervention strategies in South Buton Regency. Key Word: Sanitation, Latrine, Incidence, Diarrhea, Environmental Health